Forward high-speed wireless packet data service in IS-2000 - 1×EV-DV. - Soong, A.C.K (IEEE Communications magazine)
This article describes enhancements to the physical layer design of single-carrier (1×) cdma2000® wireless networks introduced by Revision C of the IS-2000 standard (commonly referred to as 1×EV-DV). These improvements are mainly for the support of high-speed wireless packet data service on the forward (base station to mobile station) link. A new shared channel, the forward packet data channel, F-PDCH, is introduced to significantly increase spectral efficiency. This is accomplished through smart, channel-dependent scheduling of base station, BS, resources by taking advantage of the delay-tolerant nature of data traffic. This shared channel utilizes fast link adaptation through adaptive modulation and coding supported by the feedback of channel quality information. A form of hybrid ARQ type II technique commonly referred to as asynchronous adaptive incremental redundancy compensates for frame error events due to imperfect link adaptation. The impact of the new channel on voice capacity of the system is designed to be minimal because the F-PDCH utilizes resources that are not consumed by real-time users.